2014
DOI: 10.1021/nl502837d
|View full text |Cite
|
Sign up to set email alerts
|

Friction of Water on Graphene and Hexagonal Boron Nitride from Ab Initio Methods: Very Different Slippage Despite Very Similar Interface Structures

Abstract: Friction is one of the main sources of dissipation at liquid water/solid interfaces. Despite recent progress, a detailed understanding of water/solid friction in connection with the structure and energetics of the solid surface is lacking. Here we show for the first time that ab initio molecular dynamics can be used to unravel the connection between the structure of nanoscale water and friction for liquid water in contact with graphene and with hexagonal boron nitride. We find that whilst the interface present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

59
391
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 374 publications
(458 citation statements)
references
References 51 publications
59
391
5
3
Order By: Relevance
“…44 As compared to reference quantum Monte Carlo data, [45][46][47] it slightly overbinds water to graphene and BN, but the relative energy differences between different sites (relevant to friction) are well described (see the SI of Ref. 14 ). There are, of course, many types of defects that we could examine.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…44 As compared to reference quantum Monte Carlo data, [45][46][47] it slightly overbinds water to graphene and BN, but the relative energy differences between different sites (relevant to friction) are well described (see the SI of Ref. 14 ). There are, of course, many types of defects that we could examine.…”
mentioning
confidence: 91%
“…molecular dynamics simulations where forces are obtained from electronic structure calculations. 14,40 In particular, we have recently shown that liquid-solid friction coefficients can be computed directly from ab initio simulations, from which specific electronic structure effects on friction were revealed. 14 Here we use AIMD to investigate how defects and defect reactivity affect nanofluidic transport.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(1) is obtained based on bulk liquid. Besides, it is observed by many researchers that the true slip length is the function of not only the contact angle, but also many other factors (Wu et al 2017;Thompson and Robbins 1990;Joly et al 2006a, b;Suk et al 2008;Hilder et al 2009;Ho et al 2011;Tocci et al 2014;Secchi et al 2016). …”
Section: Calculation Of the True Slip Lengthmentioning
confidence: 99%